Kebenaran Menang Atas Kejahatan: Tinjauan Reflektif Terhadap 1 Samuel 17 - Sostenis Nggebu (Sekolah Tinggi Teologi Bethel Ambon, 2021)
This article explains that truth always reigns over evil. In the text of 1 Samuel 17 tells about Yahweh's war against evil people symbolized by the Philistines and Goliaths. The author uses the literature study method to compile this paper. In his discussion it is clear that God has acted through David to achieve this victory. The Philistines who opposed God, ridiculed and despised the Israelites as a form of resistance from the power of evil had been conquered by David as a symbol of Christ disarming the power of evil. Thus evil should have no place in the life of the believer. For God has given believers spiritual armor to resist the attacks and deceptions of the Evil One. Evil has been defeated by Christ, so those who believe in Him are called to be pioneers of righteousness on earth. Believers' lives should reflect the love of Christ who has reconciled themselves to God. AbstrakArtikel ini menjelaskan tentang kebenaran senantiasa berkuasa atas kejahatan. Dalam teks 1 Samuel 17 mengetengahkan tentang peperangan Yahweh terhadap orang-orang yang jahat yang dilambangkan oleh bangsa Filistin dan Goliat. Penulis menggunakan metode studi literatur untuk menyusun karya tulis ini. Dalam pembahasannya tampak jelas bahwa Tuhan telah bertindak melalui Daud untuk meraih kemenangan tersebut. Orang Filistin yang menentang Allah, mencemooh dan merendahkan orang orang Israel sebagai bentuk perlawanan dari kuasa kejahatan telah ditaklukan Daud sebagai lambang dari Kristus yang melucuti kekuasaan kejahatan. Dengan demikian kejahatan semestinya tidak memiliki tempat dalam hidup orang percaya. Sebab Tuhan telah memberikan perlengkapan senjata rohani bagi orang percaya untuk melawan serangan dan tipuan dari Si Jahat. Kejahatan telah dikalahkan Kristus maka orang yang percaya kepada-Nya dipanggil untuk menjadi pelopor kebenaran di muka bumi. Hidup orang percaya seyogianya mencerminkan kasih Kristus yang telah mendamaikan diri mereka dengan Allah.